Kesalahan Berbahasa Bidang Fonologi Dan Morfologi Dalam Penulisan Surat Dinas Di Smk Harapan Kartasura - Purwaningsih, Setyo, Dra. Atiqa Sabardila,M.Hum (2016)
This study aims to (1) describe the phonological field of language errors in the writing department at SMK Harapan Kartasura, (2) describe the morphological field of language errors in the writing department at SMK Harapan Kartasura. The method use in this research is descriptive qualitative. This is a source of research data in official letter SMK Harapan Kartasura totaling fifteen letters. Data form this study is the word of phrase that is experiencing the error phonology and morphology in the department at SMK Harapan Kartasura. The method use was a data analysis agih method. From results of this study are error speaking areas of phonology and morphology. The dominant error is an the field of phonology reach 48 errors. Phonology errors found are errors capitalization, errors use of italics, misuse of the emblem numbers, phoneme pronuncation error,misapplication absorption elements and word errors. Morphological errors found some six errors. Morphological errors include errors due to redundandy, errors affixation, and writting error preposition.